Laparoscopic Totally Extraperitoneal (TEP) Groin Hernia Repair in Patients After Contralateral TEP Groin Hernia Repair. Issue 1 (24th February 2022) - Zuiki, Toru; Ohki, Jun; Miyahara, Go; Kobayashi, Fuyumi; Lefor, Alan K.
Abstract : Background: The totally extraperitoneal (TEP) repair for groin hernia is considered difficult in patients with a healed surgical scar in the lower abdomen. We reported the feasibility of repair in those patients and found that the most frequent previous procedure in patients for whom the procedure was changed intraoperatively was a contralateral TEP after TEP repair. We now report an expanded patient cohort with a suggested unified treatment strategy. Materials and Methods: From 2006 to 2020, 443 patients underwent laparoscopic TEP groin hernia repair. A contralateral TEP after TEP repair was performed in 35 patients. The conversion rate after TEP was compared with that after other operations. Patients were divided into completed contralateral TEP after TEP repair (N=28) and changed procedure groups (N=7). Clinical characteristics were compared including age, body mass index, location and type of hernia, and interval after previous surgery. Multivariate analysis was performed to evaluate risk factors for conversion of the TEP procedure. Results: Patients undergoing contralateral TEP after TEP repair were significantly overrepresented among patients for whom the procedure was changed compared with other previous operations ( P <0.01), with an odds ratio of 19.91. Comparing completed TEP after TEP repair and changed procedure groups, there were no significant differences regarding age (mean: 67 vs. 69 y old), body mass index (22.4 vs. 22.5 kg/m 2 ), type of hernia (indirect or direct), or duration after previous TEP repair (median: 642 vs. 470 d) and identified no significant risk factors. Conclusions: The contralateral TEP after TEP repair for groin hernia is feasible. However, dense adhesions may be present if balloon dissection was performed at the previous TEP repair, and it is necessary to carefully dissect being ready to convert to other procedures such as TAPP repair or an anterior approach.